Influência da rota dos vinhos no enoturismo do Algarve - Serra, Cristiana (2015)
This article aims to approach the Wine Route in Algarve, while fueling the Enotourism in the Region. In methodological therms, secondary sources were consulted, including literature considered relevant, as well the analysis of the case Tenerife, as a destination where Enotourism was successfully implemented. The primary sources used for the case study were based on an analysis of interviews to the producers associates to the Algarve Wine Route (AWR) and an interview with the head of AWR, which led to the view and vision of the leaders in the implementation of this project. In order to give greater depth to the theme addressed the issue of external promotion of wine tourism, verifying which markets to consider in attracting tourists for using such statistics and information listed on the Portuguese Tourism Website. The main results point to the need for continuity the consolidation and reinforcing the AWR, increasing the collaboration between partners and among economic actors. In the opinion of the respondents, the external markets are the major destination for both the flow of wine production, as for attracting new customers and as such should be treated as strategic markets.